Evaluation of dysplasias associated with inflammatory bowel disease—a single-center, retrospective, 5-year experience - Zsófia Balajthy; Panna Szaszák; Szintia Almási; Tamás Lantos; Anita Sejben (Pathology and Oncology Research)
IntroductionSeveral novel morphological variants of inflammatory bowel disease (IBD)- associated dysplasias have been described in recent years. The objective of our study was to reevaluate some of our IBD-associated neoplasia cases and retrospectively identify the so-called non-conventional dysplasias (NCDs).MethodsWe established a database of IBD patients registered between 2011 and 2015 at the Department of Pathology, University of Szeged. Patients with neoplastic samples were extracted into a separate database. Clinical and pathological characteristics were documented for each case. Histological slides were retrospectively reviewed, and cases were reclassified.ResultsDuring the study period, 57 patients had neoplastic samples, and 47 patients were identified with conventional dysplasias (82.5%). A significant association was found between conventional dysplasias and dysplasia localization (P = 0.004), size (P = 0.012), endoscopic appearance (P = 0.006), grade (P = 0.011), macroscopic appearance of colorectal carcinoma (P = 0.009), and pT stage (P = 0.01). NCD was identified in 20 cases (35.1%). The most frequently observed subtype was serrated not otherwise specified (NOS) dysplasia (n = 6; 30%). Significant associations were detected between the development of NCD and several clinical-pathological features, including the occurrence (P < 0.001), localization (P = 0.001), size (P = 0.002), macroscopic appearance (P = 0.01), grade (P = 0.005), histological subtype (P = 0.003), pT (P = 0.003) and pM stage (P = 0.047) of colorectal carcinoma, as well as microsatellite status (P < 0.001).DiscussionThe identification of IBD-associated NCDs might play a crucial role in future clinical practice. Some authors suggest closer patient follow-up upon identification of these lesions and recommend random biopsy sampling in IBD patients to detect potentially occult lesions. Further studies involving larger national and international patient cohorts are warranted to gain a more comprehensive understanding of the clinical behavior of NCDs.